Detection of Treponema pallidum in the vitreous by PCR. Issue 5 (15th November 2006) - Müller, M; Ewert, I; Hansmann, F; Tiemann, C; Hagedorn, H J; Solbach, W; Roider, J; Nölle, B; Laqua, H; Hoerauf, H
Abstract : Background: Ocular involvement of syphilis still poses a clinical challenge due to the chameleonic behaviour of the disease. As the serodiagnosis has significant limitations, the direct detection of Treponema pallidum (TP) in the vitreous represents a desirable diagnostic tool. Methods: Real-time polymerase chain reaction (PCR) for the detection of TP was applied in diagnostic vitrectomies of two patients with acute chorioretinitis. Qualitative verification of TP by real-time PCR and melting point analysis according to a modified protocol was ruled out. Patients underwent complete ophthalmological examination with fundus photographs, fluorescein angiography, serological examination, antibiotic treatment and follow-up. Results: In two cases of acute chorioretinitis of unknown origin, real-time PCR of vitreous specimens of both patients provided evidence of TP and was 100% specific. Initial diagnosis of presumed viral retinitis was ruled out by PCR of vitreous specimen. Patients were treated with systemic antibiotics and showed prompt improvement in visual function and resolution of fundus lesions. Conclusions: With real-time PCR, detection of TP in the vitreous was possible and delivered a sensitive, quick and inexpensive answer to a disease rather difficult to assess. In cases of acute chorioretinitis, the use of PCR-based assays of vitreous specimens in the diagnostic evaluation of patients is advisable. Although syphilitic chorioretinitis is a rare disease, PCR should include search for TP, as diagnostic dilemmas prolong definitive treatment in a sight-threatening disease.